Formal Attribute Specification Template To Elicit Accurate Automotive Requirements - Akmal, Suriati; Kamalrudin, Massila; Safiah, Sidek (2015)
Due to complexity of customer’s requirements and drastic technological changes, today’s development of automotive product is becoming complex and requires intensive knowledge and information. The accurate knowledge and information focusing on products and processes are crucially required to avoid mismatch information that affect the production of products that meet customer’s requirements. Unfortunately, the current approach of eliciting knowledge and information that describes the common attributes of automotive products is problematic as it lacks formalism of automotive products. In this study, we propose the use of ontology to represent the knowledge of automotive products. This paper presents an approach to describe the common attributes of automotive products using a Formal Attribution Specification Template (FAST). The attributes identified by FAST is a formal attributes that can be used to develop ontology. The formal attributes are expressed in terms of its mereological and topological structure and it involves with one or more processes. Our study shows that FAST is efficient and useful for describing automotive attributes, which can improve the elicitation of accurate automotive requirements and provides the design rationale of ontology.